Functional Modules in Gametogenesis - Kikuchi, Mariko; Tanaka, Minoru (Frontiers in Cell and Developmental Biology, 2022)
Gametogenesis, the production of eggs and sperm, is a fundamental process in sexually reproducing animals. Following gametogenesis commitment and sexual fate decision, germ cells undergo several developmental processes to halve their genomic size and acquire sex-specific characteristics of gametes, including cellular size, motility, and cell polarity. However, it remains unclear how different gametogenesis processes are initially integrated. With the advantages of the teleost fish medaka (Oryzias latipes), in which germline stem cells continuously produce eggs and sperm in mature gonads and a sexual switch gene in germ cells is identified, we found that distinct pathways initiate gametogenesis cooperatively after commitment to gametogenesis. This evokes the concept of functional modules, in which functionally interlocked genes are grouped to yield distinct gamete characteristics. The various combinations of modules may allow us to explain the evolution of diverse reproductive systems, such as parthenogenesis and hermaphroditism.